Association Analysis of Genetic Variant of rs13331 in PSD95 Gene with Autism Spectrum Disorders：A Case-control Study in a Chinese Population - 王佳 李丽 邵珊珊 何珍 陈艳琳 孔锐 张晓慧 龚建华 宋然然 (Journal of Huazhong University of Science and Technology. Medical sciences, 2016)
Autism spectrum disorder（ASD） is a neurodevelopmental disorder characterized by high heritability. Recently, autism, the most profound form of ASD, has been increasingly attributed to synaptic abnormalities. Postsynaptic density 95（PSD95）, encoding PSD protein-95, was found essential for synaptic formation, maturation and plasticity at a PSD of excitatory synapse. It is possibly a crucial candidate gene for the pathogenesis of ASD. To identify the relationship between the rs13331 of PSD95 gene and ASD, we performed a case-control study in 212 patients and 636 controls in a Chinese population by using a polymerase chain reaction-restriction fragment length polymerase（PCR-RFLP） assay. The results showed that in genetic analysis of the heterozygous model, an association between the T allele of the rs13331 and ASD was found in the dominant model（OR=1.709, 95% CI 1.227–2.382, P=0.002） and the additive model（OR=1.409, 95% CI=1.104–1.800, P=0.006）. Our data indicate that the genetic mutation C〉T at the rs13331 in the PSD95 gene is strikingly associated with an increased risk of ASD.